Key Sectors. A New Proposal From Network Theory - Ana Salome Garcia Muniz; Antonio Morillas Raya; Carmen Ramos Carvajal (European Regional Science Association (ERSA), 2006)
The determination of key sectors (Perroux, 1955; Hirschman, 1958) has raised a long tradition of studies in the input-output field. Their analysis allows the identification of those sectors has a high effect in the demand and supply of the system and therefore, they constitute the basis of the growth and development of a territory. With the aim of standing out those sectors with a more relevant position in the economy, we propose from the network theory a definition of centrality that we consider it is new new in the input-output field. This definition is based in the consideration of three complementary characteristics: total effects, mediative effects and inmediate effects. These measures called for us multilevel indicators have the enormous advantage of allowing the comparison between structures of different size and approach the key sector concept thorough a relational and global view.
Keywords: 330